Digital Option Valuation With the SABR Model. Issue 107 (30th May 2020) - Hagan, Patrick S.; Lesniewski, Andrew S.; Skoufis, G. E.; Woodward, Diana E.
Abstract : We analyze the valuation of European digital call and put options in the market standard SABR stochastic volatility model. Asymptotic methods developed for the arbitrage‐free SABR model are used to obtain explicit, closed‐form formulae for the valuation of European digital call and put options under the SABR model. Results derived in this paper have the same order of accuracy as the closed‐form SABR formulae, and they exactly satisfy put‐call parity for digital options.